Collective Identities, Black Girlhood and 60s Vocal Groups. Issue 1 (1st March 2022) - Berney, Apryl
Abstract: Drawing on interviews with Black women who sang in all-female vocal groups during the late 1950s and early 1960s, I examine the important role played by integrated public and private schools in the formation of the 1960s girl group phenomenon. From talent shows to choir practice, locker rooms to hallways, Black girls took up audible space in institutions of higher learning whenever they harmonized with friends or acquaintances. The collective identities Black girls created in their vocal groups allowed them to challenge racial and gender stereotypes in the civil rights era while also modeling sisterhood and friendship for subsequent generations of girls.